Biohydrogen production from palm oil mill effluent via sequential dark-photo fermentation - Mishra, Puranjan (2018)
Fermentative hydrogen production using biomass (a product of photosynthesis) is a promising route toward the sustainable bioenergy production. A novel concept of two stage-sequential dark-photo fermentation (TSDPF) system was proposed for enhanced biohydrogen production and CODremoval using palm oil mill effluent (POME) as fermentative substrate. The main objective of this study comprises the hydrogen production in batch mode from POME using TSDPF system. In the initial stage of the study, isolation of an indigenous hydrogen producing strain, ‗Bacillus strain PUNAJAN1‘ was done using POME sludge. The analytical data of various physicochemical parameters indicated the maximum biohydrogen production of 2.42 mol H2/mol hexose at optimal temperature of 35°C, pH 6.5, 1.2 g L-1 of NH4Cl (as a nitrogen source) and 10 g L-1 of mannose (as carbon source). Besides, the strain PUNAJAN1 has also shown the efficient hydrogen production ability of 0.23 L-H2/gCODremoved, when POME was subjected as a carbon source. Further, hydrothermally prepared nickel (NiO NPs) and cobalt oxide nanoparticles (CoO NPs) were added to POME with the range of 0.25 to 3.0 mg L-1 POME. Results demonstrated 1.51 and 1.67 folds of noticeable enhancement in biohydrogen production from POME supplemented with 1.5 mg L-1 NiO NPs and 1.0 mg L-1 CoO NPs respectively, in comparison to the control. Furthermore, a statistical approach to optimize the production of photofermentative H2 from dark fermented POME using Box–Behnken response surface methodology. Experimental data has shown a positive correlation between interdependence among various parameters (such as dilution of DPOME, initial pH and agitation regime) with improved photo-H2 production, as significant enhancement of hydrogen yield from 0.79 to 3.11 mol-H2/mol-acetate was observed under the optimal condition of 40% of dilution of DPOME; pH 6.0; and agitation rate of 140 rev/min. The observed enhancement in photohydrogen production from DPOME under optimized conditions was almost fivefold. Finally, feasibility of TSDPF system in enhancing photo-H2 production using POME has been successfully validated, where first stage fermentation was carried out using PUNAJAN1 strain (resulted 41% of CODremoval along with hydrogen yield of 37.11 ml H2/g-COD) followed by second stage fermentation using 40% diluted DPOME with sterilized tap water (photo-fermentation). Applicability of using TSDPF system in increasing hydrogen yield (from 37.11 to 130.89 ml H2/g-COD) and CODremoval rate (from 41 to 93%) has been implicated in this study which is reportedly far superior to single stage dark fermentation of POME. So, these results confirmed an effectual utilization of sequential dark-photo fermentation using dark POME can result in substantial hydrogen production and CODremoval.